TANGGUNG JAWAB NOTARIS/PPAT TERHADAP AKTA YANG DIBATALKAN OLEH PENGADILAN (Studi Kasus Putusan Nomor 35/PDT/2021/PT.DPS.) - Ghozy Ahmad Rasyid (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this research is: first, to analyze the responsibility of a Notary/PPAT when a deed they have made is canceled by the Court. Second, to analyze the legal consequences that arise after a Notary/PPAT deed is canceled by the Court. There are two problem formulations in this research: 1) What are the legal consequences of canceling a Notary/PPAT deed?, 2) What is the responsibility of a Notary/PPAT for the cancellation of the deed? This research is a normative juridical legal research, meaning the approach is carried out by examining or researching theoretical approaches, concepts, laws and regulations related to this research or regulatory approaches. The results of this research; first, with the cancellation of a Notary/PPAT deed, all deeds related to the deed are canceled and have no legal force. Second, when a deed is canceled due to an error by the Notary/PPAT, the above can be held accountable, however, when the error is from the parties, the Notary/PPAT should not get involved in the dispute.